Improving the Mapping of Moise+ to Colored Petri Nets - Machado, Ricardo A.; Adamatti, Diana F.; Gonçalves, Eder M. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2023: Anais do XVII Workshop-Escola de Sistemas de Agentes, seus Ambientes e AplicaçõesDO - 10.5753/wesaac.2023.33439, 2023)
The demand for systems with artificial intelligence such as Multiagent Systems (MAS) is continuously growing. At the same time, the need for the development of tools that help software development increases, ensuring better fault tolerance for the project, since these systems have characteristics that make the system non-deterministic and increase the difficulty in carrying out tests. In previous work, an approach was presented for tests in MAS that use the organizational model Moise+, where test cases were generated using Colored Petri Nets (CPN) to map the system in a formal model. In this work, an update is presented for the inclusion of more elements contained in Moise+ that will be mapped in the CPN, more specifically, the minimum and maximum cardinality for each existing mission.